2012
DOI: 10.1128/jvi.06200-11
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody-Based Antigenic Mapping of Norovirus GII.4-2002

Abstract: Noroviruses are the primary cause of epidemic gastroenteritis in humans, and GII.4 strains cause ϳ80% of the overall disease burden. Surrogate neutralization assays using sera and mouse monoclonal antibodies (MAbs) suggest that antigenic variation maintains GII.4 persistence in the face of herd immunity, as the emergence of new pandemic strains is accompanied by newly evolved neutralization epitopes. To potentially identify specific blockade epitopes that are likely neutralizing and evolving between pandemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 50 publications
5
161
0
Order By: Relevance
“…For example, in the case of HIV, with the aid of an extra long CDR3 loop, the neutralizing Nanobody D7 effectively competed for the CD4 binding site on gp120 protein [42]. Previously described Nanobodies and mAbs with therapeutic potential against human norovirus were also proposed to interfere with the HBGA binding site [20,[22][23][24][25][26][27]. MAb termed NV8812 bound to a conformational epitope on the GI.1 P domain and blocked the binding of norovirus VLPs to human and animal cell lines [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the case of HIV, with the aid of an extra long CDR3 loop, the neutralizing Nanobody D7 effectively competed for the CD4 binding site on gp120 protein [42]. Previously described Nanobodies and mAbs with therapeutic potential against human norovirus were also proposed to interfere with the HBGA binding site [20,[22][23][24][25][26][27]. MAb termed NV8812 bound to a conformational epitope on the GI.1 P domain and blocked the binding of norovirus VLPs to human and animal cell lines [24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that antibodies targeting the HBGA pocket could inhibit norovirus replication by steric interference with the GI.1 HBGA pocket [22]. A number of other studies have identified norovirus-specific monoclonal antibodies (mAbs) and single chain variable domains (VHH or Nanobodies) that could block norovirus VLP binding to HBGAs [20,[23][24][25][26][27]. However, most of these antibodies and Nanobodies are genotype specific, which limits their therapeutic potential [28].…”
Section: Introductionmentioning
confidence: 99%
“…11 Residues of the P2 subdomain of GII.4 are described to be under selective pressure and consequently leading to antigenic drift resulting in escape of the immune responses. 28,29,38,40 In summary, antigenic drift, strain recombination, 35 antigenic shift and the polymerase fidelity of NoVs 43 clearly contribute to the continuous propagation of GII.4. The evolution of GII.4, described as being epochal (long periods of status quo followed by outbursts of variation) over time generates escape mutants that are periodically selected for by herd immunity.…”
Section: Viral Diversitymentioning
confidence: 99%
“…28,29 Expression of the VP1 capsid as a recombinant protein independently of other viral parts leads to self-assembly into a virus-like particle (VLP). The latter has structural and antigenic characteristics that cannot be distinguished from the virus.…”
Section: Viral Diversitymentioning
confidence: 99%
See 1 more Smart Citation